Investment Analysis of Smart Connected Motorbike in Machine to Machine Application in Indonesia - Jarot S Suroso; Eva Nurul Jamilah (IAES Indonesia Section, 2018)
At present the cellular operator is faced with difficult conditions, where the customer growth rate is at its peak. In terms of income, there was also a decline in growth because legacy services (voice & SMS) tended to decline due to threats from OTT. Therefore, a strategy is needed to survive this condition, one of which is to look at the digital market. The digital service business development strategy is carried out to be able to increase the company's revenue through the implementation of Machine to Machine (M2M) services given the promising potential and support of the digital ecosystem. But in reality, the implementation of digital services has not been able to have a significant impact on the company's revenue growth so that a new strategy is needed with a service innovation. This study aims to model M2M digital services into the Smart Connected Motorbike (SCM) service, as well as analyze the service delivery business model in the PT. XYZ so that it is expected to become a new source of income for cellular operators of PT. XYZ. Furthermore, this research will do investment analysis in machine to machine application. Moreover, this research also indicated that this implementation is also feasible to increase the company's earnings.